Tetradecanuclearity in 3d–4f chemistry: relaxation and magnetocaloric effects in [NiII6LnIII8] species. Issue 11 (21st February 2017) - Canaj, Angelos B.; Kalofolias, Dimitris A.; Siczek, Milosz; Lis, Tadeusz; McNab, Robbie; Lorusso, Giulia; Inglis, Ross; Evangelisti, Marco; Milios, Constantinos J.
Abstract : The syntheses, structures, relaxation and magnetocaloric properties of two new hetero-tetradecametallic 3d–4f complexes are reported. Abstract : The employment of 2-amino-isobutyric acid, Haib, and 2-hydroxy-1-naphthaldehyde, Hnaphth, in Ni II /Ln III chemistry has led to the isolation and characterization of two new isostructural 3d–4f tetradecanuclear [NiII6LnIII8] clusters (Ln = Gd III, Dy III ), with the Dy analogue displaying temperature and frequency dependent out-of-phase signals, and the Gd analogue showing interesting magnetocaloric properties.